THE ROLE OF PHYSICAL EDUCATION TEACHERS IN THE SPORTS DEVELOPMENT AND COACHING SYSTEM IN PURWAKARTA DISTRICT - Rusandi, D. (ASEAN Journal of Sport for Development and Peace, 2024)
This research aims to systematically analyze the role of physical education teachers in the sports development and coaching system in the Purwakarta District. This research method uses the Systematic Literature Review method. Data was collected from various databases, such as Google Scholar and Scopus. The hypothesis is expected to show that physical education teachers have an essential role in the sports development and coaching system in Purwakarta District. The role of a physical education teacher includes motivator, organizer, as a coach, as a coach, and as a facilitator. The quality of physical education teachers influences the effectiveness of the sports development and coaching system. Based on the research results, it can be concluded that physical education teachers have an essential role in the sports development and coaching system in Purwakarta District. The quality of physical education teachers influences the effectiveness of the sports development and coaching system. Efforts need to be made to improve the quality and training of physical education teachers, provide facilities and adequate sports infrastructure, provide financial support for awards for outstanding physical education teachers, building collaboration between schools, local governments and sports organizations so that they can produce a healthy, fit and high-achieving young generation